2021
DOI: 10.1155/2021/2637439
|View full text |Cite
|
Sign up to set email alerts
|

An Immersive Context Teaching Method for College English Based on Artificial Intelligence and Machine Learning in Virtual Reality Technology

Abstract: With the development of language research and language teaching, people realize that grammatical competence is an important part of communicative competence. In foreign language teaching, grammar teaching is not only necessary but also the main way to achieve the goal of communicative competence. This article mainly studies the virtual reality technology college English immersive context teaching method based on artificial intelligence and machine learning. The purpose is to improve students’ English learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 26 publications
0
54
0
2
Order By: Relevance
“…It can not only deepen the memory of knowledge but also cultivate rich 3D reconstruction capabilities. It is generally difficult to make 3D models [ 28 ]. The staff summarized several conclusions about the application of VR technology in medical education: (1) It improves the intuition and interest of medical knowledge, and interest is a factor of student enthusiasm and initiative.…”
Section: Experiments and Analysismentioning
confidence: 99%
“…It can not only deepen the memory of knowledge but also cultivate rich 3D reconstruction capabilities. It is generally difficult to make 3D models [ 28 ]. The staff summarized several conclusions about the application of VR technology in medical education: (1) It improves the intuition and interest of medical knowledge, and interest is a factor of student enthusiasm and initiative.…”
Section: Experiments and Analysismentioning
confidence: 99%
“…All studies reported positive effects of AI in general (see Appendix). Specifically, studies found (1) comprehensive improvement of student's English level (e.g., Bin & Mandal, 2019;L. Ma, 2021), (2) proven usability and suitability of the platform/interface (e.g., Li, 2017;Yuan, 2021) 16) improvement in accuracy of facial recognition (e.g., Y.…”
Section: State Of Current Research On Ai In Eltmentioning
confidence: 99%
“…As far as the duration of the experiment is concerned, Ma's study [12] lasted the whole semester, making it the most extended study in this review, and it is essential when compared to the other studies where there was little interaction with the technology. After a semester of instruction, the two groups were given a final English exam that included listening, speaking, grammar, reading comprehension, and writing.…”
Section: Procedures Findings and Limitationsmentioning
confidence: 99%